THU0274 An Inception Cohort of Chinese Patients with Antineutrophil Cytoplasimic Antibody-Associated Vasculitis in a Tertiary Centre in Hong Kong – a Study of Clinical Manifestations, Survival and Prognostic Factors. (9th June 2015) - Ho, C.H.
Abstract : Background: Despite advancement in the treatment of ANCA-associated vasculitis (AAV), there are still considerable morbidities and mortalities resulting from treatment-related complications. Overseas studies have identified various prognostic factors of AAV to stratify patients' risks and thus to determine the suitable treatment strategy 1, 2 . Given the difference in epidemiology of AAV over the world 3, a new scoring system for prognostication of AAV local population is needed. Objectives: To review the clinical profile and survival of AAV in local Chinese population and to look for any predictors of mortality Methods: 81 patients with AAV diagnosed between January 2000 and December 2012 were included. Demographic data, background medical comorbidies, clinical data related to AAV were reviewed and compared with overseas studies. Survival was analysed with Kaplan-Meier method and Cox proportional hazards model. Predictors of mortality were determined by multivariate analysis. Survival stratified according to the numbers of poor prognostic factors was analysed with Kaplan-Meier method. Results: Median age of diagnosis was 69-year-old, older than that in European data (58-64 years old) 4 . Median survival was 80 months. Top causes of death were infection, active vasculitis and cardiovascular events. Overall 1-year and 5-year mortality of AAV in local population were 87% and 52% respectively, similar to and worse than those reported in European trials respectively 4 . Age ≥68-year-old (HR 3.99, p=0.008), haematuria (HR 3.42, p=0.007), pulmonary haemorrhage (HR 10.02, p=0.003), underlying cardiovascular risk factors (HR 2.71, p=0.024) and pre-existing malignancy (HR 3.95, p=0.018) were found to be significant predictors of overall and 12-month mortalities. Plasma exchange was associated with a lower risk of 12-month (HR 0.126, p=0.022) and in-hospital mortalities (HR 0.08, p=0.025). Pulmonary haemorrhage is the only factor predicting in-hospital mortality (HR 46.3, p=0.0030). The 1-year mortality rates of patients with 0, 1 and ≥2 poor prognostic factors were 0%, 15% and 51% respectively; and the 5-year mortality rates were 0%, 19% and 74% respectively. (p<0.001). Conclusions: Local Chinese patients with AAV tended to be older than their western counterparts. Factors predicting mortality were also different between both groups. A strategy of tailoring treatment according to disease severity should be adopted to balance between adequate disease control and prevention of treatment-related complications. References: Guillevin L, Pagnoux C, Seror R, Mahr A, Mouthon L, Le Toumelin P. The Five-Factor Score revisited: assessment of prognoses of systemic necrotizing vasculitides based on the French Vasculitis Study Group (FVSG) cohort. Medicine (Baltimore). 2011;90(1):19–27. Flossmann O, Berden A, de Groot K, et al. Long-term patient survival in ANCA-associated vasculitis. Ann Rheum Dis. 2011;70(3):488–94. Fujimoto S, Watts R a, Kobayashi S, et al. Comparison of the epidemiology of anti-neutrophil cytoplasmic antibody-associated vasculitis between Japan and the U.K. Rheumatology (Oxford). 2011;50(10):1916–20. Mukhtyar C, Flossmann O, Hellmich B, et al. Outcomes from studies of antineutrophil cytoplasm antibody associated vasculitis: a systematic review by the European League Against Rheumatism systemic vasculitis task force. Ann Rheum Dis. 2008;67(7):1004–10. Disclosure of Interest: None declared